A comparison between chemical and gas hypoxia as models of global ischemia in zebrafish (Danio rerio). Issue 3 (10th August 2020) - Marino, Kaitlyn M.; Silva, Emani R.; Windelborn, James A.
Abstract: Background: Zebrafish models for neurovascular diseases offer new methods for elucidation of molecular pathways to tissue damage. External fertilization and high fecundity provide opportunities for transgenics and other forms of genetic manipulation that are more accessible than offered by mammalian models of disease. Furthermore, behavioral analyses of zebrafish allow for connection of molecular pathways to organismal outputs such as locomotion, learning, and memory. Unfortunately, a zebrafish model of hypoxia‐ischemia has been slow to catch on, possibly due to hypoxia exposure protocols that are challenging to reproduce and result in high mortality. Methods: In this study, we have introduced a predictable and simple method of hypoxia induction, the addition of sodium sulfite to aquarium water. The effects of this treatment on zebrafish locomotion were compared to those of zebrafish exposed to hypoxia induced by nitrogen gas bubbling, a method used in previous reports. Results: We found that hypoxia induced by sodium sulfite significantly impaired locomotion in the hours following treatment, and its effects did not differ from those caused by nitrogen gas hypoxia. Conclusion: These results indicate that hypoxia by sodium sulfite represents an effective and easily reproducible method for the study of hypoxia‐ischemia in zebrafish.